Assessment Of Quarry Environmental Modeling Software Version 2.0 (QEMS V2.0) For Estimation Of Noise At Crusher Boundary - Abdul Halim, Muhammad Helmi (Universiti Sains Malaysia, 2018)
Noise emission is one of the main problems faced by quarries throughout the world due to the health effects towards surrounding societies. The worst case when the emissions of noise that fall into the hazardous range which is above 85dB, which have been shown to cause more severe health effect. The severe health effect can be in emotional disturbance, hearing impairment and also hearing loss. In quarry operation, commonly crusher produced an excessive noise emission. However, the Department of Environment (DOE) Malaysia has established the regulation of noise to control this phenomenon. Furthermore, all quarries in Malaysia have been practice noise monitoring as the requirement by regulations. Based on this study in Simpang Pulai, Perak, this written paper was the idea of develop a new prediction model to predict the sound emission at crusher boundary. This model will be verified by another software namely QEMs Version 2. All the data collected were analyzed using IBM SPSS 13.0 software package. The results of the analysis on new model has been made and showed the R2 is 0.139 which indicates that meteorological variables do not heavily effects on the noise. While the comparison on both models with actual noise level resulted the QEMs had value of R2is 0.627 which is better than new prediction model.